Manure Unggas: Suplemen Pakan Alternatif dan Dampak terhadap Lingkungan - Yanuartono, Yanuartono; Nururrozi, Alfarisa; Indarjulianto, Soedarmanto; Haribowo, Nurman; Purnamaningsih, Hary; Raharjo, Slamet (BPPT, 2018)
The increase in protein demand is now of serious concern as the human population is forecasted to rise to as much as 9.6 billion by 2050. The poultry industry is one of the largest and fastest growing sectors of livestock production in the world. Increased production results in increased sewage so that the impact on the emergence of envir onmental problems associated with increased air pollution, water, and soil. The sustainability of animal feeds is crucial in the development of livestock production systems, and feed efficiency can be improved by reusing poultry waste in livestock diets, t hus diminishing the use of feed grains. There are several ways of disposing of poultry waste including burial, incineration, composting, fertilizer or source of biogas energy and feed for livestock. Poultry manure is a rich source of ignocelluloses, polysaccharides, proteins, minerals, and other biological materials. It is currently expected some problems can be overcome by utilizing poultry manure waste as an alternative feed source for livestock. This paper aims to review the negative effects of excessive chicken manure and its benefits as an alternative feed for livestock and fish